FORMING OF SOFT COMPETENCIES EDUCATIONAL PROCESS MANAGEMENT CHANGES (DISTANCE EDUCATION) - Ji, Fenlai; Kalashnyk, Nadiia; Chernovol-Tkachenko, Raisa; Li, Sinje; Liu, Zhijian (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The impetus and innovative idea for research was the rapid transformational changes in society. These changes were expressed in the experimental search activities of the development in education and other social and humanitarian sciences, which are now taking place in the world in connection with the COVID-19 pandemic and the maximum distanceization of processes, including educational ones. The authors concluded that these changes concern: teaching methods, organization and management of educational processes. In practical teaching, the authors noticed the peculiarities of soft competencies formation in distance learning. Unlike knowledge, soft competencies are formed in social interaction. It is completely different in content and forms of construction in online education than in the offline one. These changes in educational transformations and management of educational processes take place due to fundamental transformations under the influence of: scientific and technological progress, global security challenges, wide access to information, significant part of life virtualization, restructuring of the axis of the teaching paradigm, etc.The main idea of the article is focused on changes of soft competencies formation as they are understood in distance learning; also it was emphasized the changes, necessary for successful teachers' work management in this area. Research methods: general scientific (analysis, synthesis, collection of information, expert opinions, forecasting and modeling), special scientific (analysis of changes in law, recommended practices, observation, authors' own practice and fixation in changes in the educational results of their students).